Analisis Tata Letak dan Penerapan Sistem First In First Out Pada Gudang Barang Jadi - Risma Aulia Dewi; Fahriza Nurul Azizah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Inventory of goods is one of the company's activities that are very important for the development of the company. To implement an inventory system, there are several methods, one of which is the FIFO (First In First Out) method. FIFO is a method in which goods purchased earlier are considered to be sold or used earlier, and the cost of goods purchased earlier will be charged first as cost of goods sold. This research was conducted at PT. Samcon with the aim of providing the layout of the proposed FIFO inventory system in the finished goods warehouse of PT. The previous Samcon was less than optimal. This research is expected so that in its application it can be maximized and provide convenience and smoothness in the operational process. From this research, the area using the proposed layout results in a savings of 8.46% of the total area of ​​the finished goods warehouse. In the proposed incoming and outgoing goods flow, a one-way flow is used which makes the operator no difficulty in the process of storing, searching and retrieving finished goods so as to increase the productivity of the finished goods warehouse operator.